Hormone Therapy as a Protective Factor for Age-Related Macular Degeneration. (3rd March 2020) - Patnaik, Jennifer L.; Lynch, Anne M.; Wagner, Brandie D.; Echalier, E. Lacey; Kohrt, Wendy M.; Mathias, Marc T.; Siringo, Frank S.; Palestine, Alan G.; Mandava, Naresh
ABSTRACT: Purpose : The purpose of this study was to determine if the use of menopausal hormone therapy (HT) is related to the development of neovascular (NV) age-related macular degeneration (AMD), geographic atrophy (GA) and/or early/intermediate AMD. Methods : A case–control study was conducted from patients prospectively recruited from July 2014 to June 2019. Cases were females with AMD recruited into a registry and controls were females with age-related cataract and no AMD. Age-related macular degeneration was categorized into NV-AMD, GA, and early/intermediate. Hormone therapy (historic and current) was self-reported by the patient and categorized as ever/never use. Adjusted odds ratios (ORs) from multinomial logistic regressions are presented for each AMD group. Results : Female AMD case patients (n = 409) and controls (n = 132) were included in the analytic database. Almost half (45.5%) of the female AMD patients had NV-AMD, 14.9% had GA, and 39.6% had early/intermediate AMD. Among all study participants, 285 (52.7%) reported historic and/or current use of HT. Controls were significantly more likely to have any HT use (71.2%), compared to 43.0% (p ≤ 0.001) of NV-AMD patients, 47.5% ( p = .002) of GA patients, and 50.6% (p ≤ 0.001) of early/intermediate AMD patients. Adjusted for potential confounders of age and Caucasian race, cases were significantly more likely to have lower HT use compared to controls: NV-AMD, OR = 0.31 (95%CI: 0.18–0.54), GA, OR = 0.40 (95%CI: 0.20–0.80), and early/intermediate AMD, OR = 0.36 (95%CI: 0.22–0.61). Conclusion : Our case–control study found that the use of HT was associated with a lower odds of all AMD stages studied: NV-AMD, GA and early/intermediate.